Critical Thinking and ICT Integration in a Western Australian Secondary School - McMahon, Graham (Massey University, New Zealand, 2009)
This study examined the relationship between students working in a technology-rich environment and their development of higher order thinking skills. Based on a PhD thesis, which examined a greater range of relationships than can be reported here, this article focuses on developing critical thinking skills within a technology-rich environment. Staff and students from one school participated in the study. Data were collected to determine the degree of correlation between factors of the learning environment and the extent to which critical thinking skills were demonstrated by the students. Statistical correlations allowed relationships between environmental factors and critical thinking to be established. The results indicate that there are statistically significant correlations between studying within a technology-rich learning environment and the development of students' critical thinking skills. Length of time spent in the environment has a positive, non-linear effect on the development of critical thinking skills. Students with better developed computing skills scored higher on critical thinking activities. This was most significant for students with better computer programming skills and the ability to competently manipulate Boolean logic. The research suggests that to develop students' higher order thinking skills, schools should integrate technology across all of the learning areas. This will allow students to apply technology to the attainment of higher levels of cognition within specific contexts. This will need to be paralleled by providing students the opportunity to develop appropriate computer skills.